Ultrasound-guided subclavian vein catheterisation with a needle guide (ELUSIVE): protocol for a randomised controlled study - Maria Adrian; Ola Borgquist; Thomas Kander; Leila Naddi; Björn P Bark (BMJ Open)
Introduction Central venous catheters are indispensable in modern healthcare. Unfortunately, they are accompanied by minor as well as major complications, leading to increased morbidity, mortality and costs. Immediate insertion-related complications (mechanical complications) have decreased due to the implementation of real-time ultrasound guidance, but they still occur and additional efforts to enhance patient safety are warranted. This study aims to investigate whether the use of a needle guide mounted on the ultrasound probe in subclavian catheterisations may decrease the number of catheterisations with >1 skin puncture (primary outcome).Methods and analysis This is an investigator-initiated, non-commercial, randomised, controlled, parallel-group study conducted at Skåne University Hospital, Lund, Sweden. Adults (≥18 years) with a clinical indication for a subclavian central venous catheter and the ability to give written informed consent will be eligible for inclusion. Exclusion criteria include subclavian catheterisation deemed unsuitable based on the preprocedural ultrasound examination. Patients will be randomised to catheterisation by certified operators using a microconvex probe (long-axis, in-plane technique) with (n=150) or without (n=150) a needle guide. The ultrasound imaging from the procedures will be recorded and assessed by two reviewers individually. The assessors will be blinded for group affiliation. Secondary outcomes include the total number of skin punctures, mechanical complications, time to successful venous puncture, number of failed catheterisations and operator satisfaction with the needle guide at the end of the study period.Recruitment started on 8 November 2022 and will continue until the sample size is achieved.Ethics and dissemination This study was approved by the Swedish Ethical Review Authority (#2022-04073-01) and the Swedish Medical Products Agency (#5.1-2022-52130; CIV-21-12-038367). The findings will be submitted to an international peer-reviewed journal.Trial registration number NCT05513378, clinicaltrials.gov.